Pengembangan Instrumen Tes Multiple Choice Reasoning Terbuka Untuk Mengukur Keterampilan Berpikir Kritis Siswa - Dini Khoirunnisa Sofyan; Sabani Sabani (Journal of Natural Sciences, 2022)
This study aims to develop a HOTS-based test instrument in measuring students' critical thinking skills on the matter of effort and energy. This research is a development research or Research and Development using the ADDIE model, namely Analysis, Design, Development, Implementation and evaluation. The subjects in this study were students of class X SMAS Gema Buwana. In the content validation test by the validator the question is classified as a valid instrument. While the validity of the items obtained 9 questions are said to be valid or feasible. The reliability of the test on the questions belongs to the reliable category with a very high reliability interpretation with a result of 0.879. To test the level of difficulty of the questions obtained 1 question with easy criteria, 2 questions with difficult criteria and 6 questions with moderate criteria. While the differentiating power of the questions obtained 3 questions with improved criteria and 6 questions with accepted criteria. The effectiveness of the distractor results in 5 answer choices with rejected criteria and 31 answer choices with accepted criteria. Based on the results of the development carried out, it can be concluded that the HOTS-based open multiple choice answering test instrument is said to be feasible to measure students' critical thinking skills.